EXAMINE THE EFFECT OF SMARTPHONE USE ON SOCIAL BEHAVIOUR AND EMOTIONAL INTELLIGENCE, AMONG ISLAMIC COLLEGE LECTURER IN LUMAJANG DISTRICT - Machfudz Machfudz; Mukaffan (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
Excessive smartphone use in lecturer fourth semester in the 2025 academic year can cause cognitive, social, and emotional disorders. This article aims to examine the effect of smartphone use on social behaviour and emotional intelligence, among lecturer at three Islamic college lecturer in Lumajang district. This research is a quantitative study with an explanatory approach, focusing on a population of 95 lecturer fourth semester in the 2025 academic year. The sample collection technique used in this study is saturated sampling. Data collection in this study utilises an instrument in the form of a questionnaire, employing a Likert scale. The stages of SmartPLS analysis include creating an Outer Model (validity and reliability of the instrument), followed by an Inner Model analysis (validity and reliability of the structural model) by calculating the PLS algorithm and analysing the R-Square value, and ending with Hypothesis Testing using bootstrapping to see the significance of the relationship between variables. Smartphone use (X) has a 50.1% impact on lecturer social behaviour (Y). Smartphone use has a 53.8% impact on emotional intelligence. Keywords: smartphone use, social behaviour, emotional intelligence, lecturer